Phenotypic Diversity of a Leafroller Archips podana (Lepidoptera, Tortricidae) Does Not Change along an Industrial Pollution Gradient - Kozlov Mikhail V. (MDPI, 2025)
Simple Summary
Populations of the large fruit-tree tortrix Archips podana consist of a mixture of four morphs that differ in male genitalia traits, ecology and sexual behaviour. Here, I tested whether these morphs differently respond to pollution. I found that the within-population diversity of A. podana around the industrial city of Lipetsk in central Russia correlated neither with the distance to the nearest industrial polluter nor with the number of moths captured by pheromone traps. Thus, the four phenotypes of A. podana similarly respond to pollution.
Abstract
Morphological polymorphism offers rich opportunities for studying the eco-evolutionary mechanisms that drive the adaptations of local populations to heterogeneous and changing environments. In this study, I explore the association between pollution load, abundance of large fruit-tree tortrix Archips podana and its within-species diversity (expressed in the presence of apical and/or lateral prongs on the phallus in male genitalia) across 26 study sites located 0.5 to 31 km from the industrial city of Lipetsk in central Russia. The Shannon diversity index, calculated from the frequencies of four morphs, correlated neither with the distance to the nearest industrial polluter (a proxy of pollution load) nor with the number of moths captured by pheromone traps (a measure of population abundance). The statistical power of the correlation analysis was sufficient (67%) to detect a medium effect (i.e., Pearson correlation coefficient with an absolute value of 0.40), if it existed. I conclude that the four phenotypes of A. podana do not differ in tolerance to industrial pollution and similarly respond to pollution-induced environmental disturbance. This is the first study of industrial pollution impacts on within-species diversity of insects expressed in the discrete traits of their male genitalia.